Removal of copper by calcium alginate encapsulated magnetic sorbent - Soh-Fong, Lim; Yu-Ming, Zheng; Shuai-Wen, Zou; Chen, J.Paul (Elsevier Ltd., 2009)
In this study, the adsorption performance of copper on calcium alginate encapsulated magnetic sorbent is investigated via equilibrium and kinetics study. Results showed the sorption performance is greatly affected by the initial solution pH, the background ionic strength, the mechanical stirring speed, and the presence of humic acid. The optimum copper sorption was achieved at initial solution pH > 5. The copper uptake is poor in the presence of higher background ionic strength (sodium perchlorate). Langmuir equation can be well used to describe the adsorption isotherm data. The maximum sorption capacity (qmax) and Langmuir constant (b) decrease from 60 to 49 mg g−1 and 1.43 to 0.35 L mg−1 as the ionic strength is increased from 0 to 0.05 M. Kinetics study shows the sorption equilibrium can be obtained within 3 h, and the adsorption kinetics data are well described by the intraparticle pore diffusion model. The mechanical stirring speed greatly enhances the mass transfer rate of copper ions onto the sorbent, and the external mass transfer coefficient (kf) increases from 2.5 × 10−5 to 2.5 × 10−4 m s−1 when stirring speed is increased from 120 to 220 rpm. The presence of humic acid decreases the kf from 2.10 × 10−4 to 5 × 10−5 m s−1, and increases the time for copper to attain adsorption equilibrium due to clogging of surface pore which apparently reduce the surface reaction site.